Sources of polychlorinated dibenzo-p-dioxins and dibenzofurans, and biphenyls in Chinese mitten crabs. (April 2018) - Han, Ying; Liu, Wenbin; Zhu, Wen; Rao, Kaifeng; Xiao, Ke; Gao, Lirong; Su, Guijin; Liu, Guorui
Abstract: Polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) and polychlorinated biphenyls (PCBs) in Chinese mitten crabs from several areas were determined. The toxic equivalents (TEQs) for the mean PCDD/F and total PCDD/F and dioxin-like PCBs were 2.9 ± 2.7 and 5.7 ± 4.0 pg TEQ g −1, respectively. The mean concentrations of PCBs and dl-PCBs were 282 and 59 times the concentrations of PCDD/Fs, respectively. PCDD/F and PCB sources in the crab food web were assessed. The total TEQ of PCDD/F and PCB supplied by crab compound feed was 2.1 times the TEQ in crab meat. Broken corn, aquatic biota, and water contributed around 12% of the total TEQ inputs for crab meat. The contribution from sediment was around 164 times that from crab meat, and sediment may be the most important source of PCDD/Fs and PCBs in cultured crabs. Principal component analysis (PCA) and stable isotope ratios for nitrogen ( δ 15 N) and carbon ( δ 13 C) supported the TEQ results. The mean total PCDD/F and dl-PCB TEQ exposure for humans consuming crabs was 3.4 pg TEQ per kilogram of body weight per day. The PCDD/Fs and PCBs in >80% of the crab samples would not cause the tolerable daily intake to be exceeded. Highlights: PCDD/Fs and PCBs in Chinese mitten crabs farming from several crab-producing areas were determined. Stronger ability of bioaccumulation of PCBs than PCDD/Fs in crabs was found. Material balance was calculated to determine the contributions of different potential PCDD/F and PCB sources to the crabs. 21 non-2, 3, 7, 8-PCDD/Fs were determined in most of the brown crabmeat and sediment samples. Sediment was proposed as the most important source of PCDD/Fs and PCBs in the crabs.